Swear Word Used by Different Gender in Gangster Community as Represented in TV Series Peaky Blinders - Wahyudi Wahyudi; Arif Bima Fajar; Rosita Ambarwati; Lusia Kritiasih (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2023)
This study aims to identify the types and function of swear word TV Series Peaky Blinders.  The researcher uses a contentanalysis type with a descriptive-qualitative approach as a research method. The data of this study are gained from episode 1 – 3 of Peaky Blinders season 1. Simak dan Catat technique (listening, reading, and taking notes) was used in this study to collect data.  The researcher used the interactive model of Miles,  Huberman,  and  Saldana for data analysis,  which consists of three steps: data reduction, data display, and conclusion drawing/verification. This study finds out that found there are 86 total data swear words on episode 1 until 3 Peaky Blinders, with 70 swear words by men and 16 swear words data by women. The researcher used Hughes’s theory to analyze the type and Andersson and Trudgill’s theory to analyze the function. In conclusion. Men has more variative and goals when they are swearing than women.